Synergistic effect of combined temporal and spatial expectations on visual attention - Doherty, J; Rao, A; Mesulam, M; Nobre, A (Society for Neuroscience, 2005)
We developed a naturalistic behavioral task to investigate the influence of spatial and temporal expectations on attentional orienting to moving targets. In this task, the movement of an object before its disappearance under an occluding barrier generated expectations concerning the location and/or time of its reappearance. Four different trial types were intermixed, each inducing a different state of expectation: no expectation, only spatial expectation about the location of reappearance, only temporal expectation about the moment of reappearance, and combined spatial and temporal expectation. The behavioral validity of the task was shown by the fact that all expectation conditions produced significantly shorter reaction times than the control state of no expectation. Spatial attention modulated early perceptual analysis in extrastriate areas, as demonstrated by significant enhancement of the visual P1 component. Temporal attention alone had no effect on P1 but instead modulated response-specific components. However, when spatial and temporal attention were combined, the enhancement of perceptual processing was significantly augmented, leading to a greater enhancement of the P1 component than by spatial attention alone. Perceptual analysis reflected by the P1 component correlated significantly with reaction times. In summary, event-related potentials revealed the presence of individual modulatory effects attributable to spatial and temporal expectation as well as synergistic effects indicative of an interaction of the two. This synergistic effect is likely to play a critical role in directing attention to the reappearance of a temporarily occluded moving target, a process of obvious importance in everyday situations.